A2 milk enhances dynamic muscle function following repeated sprint exercise - Kirk, B.; Clifford, T.; Mitchell, J.; Jackson, M.; Amirabdollahian, F.; Alizadehkhaiyat, O. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Hyperaminoacidemia following ingestion of dairy-milk may stimulate muscle anabolism and attenuate exercise-induced muscle damage (EIMD). However, athletes who are dairy intolerant do not get the reported benefits from consuming milk-based products; but A2 milk may offer an alternative as it does not contain the A1-Protein. This study aimed to determine the effect of A2 milk on recovery from a sports-specific muscle damage model (Keane et al., 2015). Twenty-one male team sport players (n=21) were randomly allocated to three independent groups: (A2 milk n=7, regular milk n=7, CHO-matched placebo (PLA) n=7). Immediately following muscle damaging exercise participants consumed either A2 milk, regular milk or PLA (3 x 500ml). Visual analogue scale (muscle soreness), maximal voluntary isometric contraction (MVIC), countermovement jump (CMJ) and 20m sprint were measured pre, 24, 48, and 72 h post-EIMD. A2 and regular milk demonstrated a beneficial effect at 48h in minimising decrements in CMJ (p= 0.02 and p= 0.02, respectively) and 20m sprint (p=0.04 and p=0.03, respectively) vs. PLA. Relative to baseline, 48h CMJ and 20m sprint recovered quicker in A2 (33.4±9.6 and 3.3±1.4%, respectively) and regular milk (33.1±9.5 and 3.3±1.2%, respectively) vs. PLA (29.2±14.8 and 3.6±2.9%, respectively). Ingestion of 500ml of A2 or regular milk after muscle damaging exercise can limit decrements in dynamic muscle function in male athletes, thus hastening recovery, and increase subsequent performance; but evidently not isometric strength performance or active muscle soreness (p>0.05). The findings propose A2 milk as a suitable recovery beverage following EIMD, and may offer an alternative to athletes who experience gastrointestinal discomfort with the digestion of A1-Protein.